New hybrid system combining TEG, condenser hot air and exhaust airflow of all-air HVAC systems - Mohamad Ramadan; Samer Ali; Hasan Bazzi; Mahmoud Khaled (Case Studies in Thermal Engineering, 2017)
One of the most promising solution for the current energy crisis is recovering lost energy. Indeed, in many energy systems the percentage of energy loss could exceed 60%. To put it another way, in some applications, recovering energy is as much beneficial as finding new source of energy. Moreover, finding new concepts of energy recovery offers wider horizons to reduce energy consumption. The present work investigates new energy recovery system that combines heat recovery and energy generation using thermoelectric generators (TEG). The proposed system is a triple Thermoelectric-Energy recovery coupled system that from one hand allows to recover the heat of condenser and to reuse the lost energy of exhaust airflow of HVAC all-air system and from the other hand it permits to produce green electricity using TEG. The air of the condenser is considered the heat source, whereas the exhaust air flow is utilized as cooler. To proceed, a mathematical tool is first developed it allows to thermally simulate TEGs for different boundary conditions. The heat and cold source are then modeled where the heat transfer coefficient is determined from the Nusselt number. Furthermore, a parametric analysis is then conducted to evaluate the power generated with the new concept when the air velocity of the exhaust airflow and that of the condenser vary. It is shown that for a space cooling load of 100 kW, a 40×40 cm2 flat plate is capable to generate 90 W of electrical power.